Terlipressin Treatment for Acute Esophageal Variceal Bleeding: Bolus or Infusion? - Şenkaya, Ali; Çelik, Ferit; Kurtulmuş Akgün, İlkçe and Aslanov, Seymur and Uysal, Alper and Buyruk, Abdullah Murat and Ünal, Nalan Gülşen and Turan, İlker and Akarca, Ulus Salih and Karasu, Zeki (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This study aimed to compare the efficacy of bolus versus infusion administration of terlipressin in patients with acute esophageal variceal bleeding and to elucidate any differences in clinical outcomes between the 2 approaches. Materials and Methods: This prospective study included patients divided into 2 groups. Group 1 received a 2 mg intravenous (IV) bolus followed by 1 mg IV every 4 hours. Group 2 received a 1 mg IV bolus followed by a 4 mg terlipressin infusion over 24 hours. Clinical and laboratory parameters, hospitalization duration, need for blood product transfusion, rebleeding or mortality within 6 weeks, and drug related side effects were evaluated. Results: Among the 46 patients, 23 (50%) received terlipressin as an IV bolus (group 1), and 23 (50%) received it as an infusion (group 2). Treatment failure occurred in 4 patients (8.7%), all from group 1, though the difference was not statistically significant (P = .109). Six patients (13%) experienced rebleeding and death within 6 weeks, with no significant differences in clinical outcomes between the groups. No significant differences in creatinine and sodium levels were observed between the groups at baseline or at the end of treat ment (P = .654). Additionally, no difference in the incidence of portal vein thrombosis was noted between survivors and non-survivors (P = 1.000). Conclusion: As no significant differences in efficacy or safety were observed between bolus and infusion administration, infusion ther apy may be preferred due to its potential benefits in patient comfort and ease of administration. Cite this article as: Şenkaya A, Çelik F, Kurtulmuş Akgün İ, et al. Terlipressin treatment for acute esophageal variceal bleeding: Bolusor infusion? Turk J Gastroenterol. Published online August 25, 2025. doi: 10.5152/tjg.2025.25265.